Effectiveness of the Quantum Teaching Model in Enhancing HOTS in Fiqh at State Islamic High School - Aulia, Muhammad Ghozil; Ichsan, Ichsan; Santosa, Sedya; Rifkiya, Adiba (Indonesian Journal of Islamic Education Studies (IJIES), 2025)
The low level of Higher Order Thinking Skills and the conventional learning model applied in various schools is ineffective in improving students' HOTS, especially in Fiqh learning. This study aims to test the effectiveness of the Quantum Teaching learning model in enhancing the HOTS skills of tenth-grade students at MAN 4 Bantul. The study employs a quantitative and quasi-experimental design involving experimental and control classes. Cluster random sampling was used for sample selection. The research instruments consist of pretest and posttest questions that have been validated. Data analysis includes normality tests, homogeneity tests, t-tests, and N-Gain analysis. The results showed a significant difference between the pretest and posttest scores in the experimental class, with an average N-Gain of 68.49%, which is considered fairly effective, compared to the control class with an average N-Gain of 28.43%, which is regarded as less effective. Thus, the Quantum Teaching model has proven effective in enhancing students' HOTS skills in the Fiqh subject. This research improves HOTS of Fiqh learning students based on quantum teaching models and becomes a reference for teachers in designing learning strategies oriented towards HOTS.